1986
DOI: 10.1128/jb.167.1.153-159.1986
|View full text |Cite
|
Sign up to set email alerts
|

Role of apparent membrane growth initiation sites during photosynthetic membrane development in synchronously dividing Rhodopseudomonas sphaeroides

Abstract: Sites of intracytoplasmic membrane growth and temporal relations in the assembly of photosynthetic units were examined in synchronously dividing Rhodopseudomonas sphaeroides cells. After rate-zone sedimentation of cell-free extracts, apparent sites of initiation of intracytoplasmic membrane growth formed an upper pigmented band that sedimented more slowly than the intracytoplasmic membrane-derived chromatophore fraction. Throughout the cell cycle, the levels of the peripheral B800-850 light-harvesting pigment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…xw!y synthesized I3875 reactior! center cores of rhe photosynthetic apparatus predominantly incorporate into a distinct cytoplasmic membrane fraction from which they are then transferred into the ICM [28]. Dierstein et al [ 161 also found preferential integration of the reaction center polypeptides into a light, non-ICM membrane fraction in E. capsutatus.…”
Section: Discussionmentioning
confidence: 99%
“…xw!y synthesized I3875 reactior! center cores of rhe photosynthetic apparatus predominantly incorporate into a distinct cytoplasmic membrane fraction from which they are then transferred into the ICM [28]. Dierstein et al [ 161 also found preferential integration of the reaction center polypeptides into a light, non-ICM membrane fraction in E. capsutatus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the development of ICM is initiated by the incorporation of reaction centers and B875 complexes at specific sites into the peripheral cytoplasmic membrane (CM) (5,27,32). Some of the B800-850 complexes are added to these sites as well, but by far most of them become integrated into the developing ICM (27,28,32).…”
Section: Discussionmentioning
confidence: 99%
“…This cell-free system now offers the opportunity to study integration and assembly of pigment-binding proteins in mutant membranes lacking individual pigment-binding proteins. Furthermore, it should be suitable to address the question of the specificity of the protein insertion into distinct membrane subfractions as suggested by others (7,29). These studies should shed some light on the complex regulation of synthesis, integration and assembly of the photosynthetic apparatus from R. capsulatus.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that (a) they appear to be inserted into distinct membrane areas (7,15,29); (b) the RC is not properly assembled if the B870 complex is missing (14); (c) pigments are required for the stability and proper assembly of the protein complexes (20).…”
mentioning
confidence: 99%